Asthma, Airflow Obstruction, and Eosinophilic Airway Inflammation Prevalence in Western Kenya: A Population-Based Cross-Sectional Study - Navuluri, Neelima; Lagat, David; Egger, Joseph R.; Birgen, Elcy; Diero, Lameck; Murdoch, David M.; Thielman, Nathan; Kussin, Peter S.; Que, Loretta G.; Paul, Devon (International Journal of Public Health, 2023)
Objectives: Determine the prevalence of airway disease (e.g., asthma,airflow obstruction, and eosinophilic airway inflammation) in Kenya, as well as related correlates of airway disease and health-related quality of life. Methods: A three-stage, cluster-randomized cross-sectional study in Uasin Gishu County, Kenya was conducted. Individuals 12-years and older completed questionnaires (including St. George’s Respiratory Questionnaire for COPD, SGRQ-C), spirometry, and fractional exhaled nitric oxide (FeNO) testing. Prevalence ratios with 95% confidence intervals were calculated. Multivariable models assessed correlates of airflow obstruction and FeNO. Results: 392 participants completed questionnaires, 369 completed FeNO testing, and 305 completed spirometry. Mean age was 37.5 years; 64% were women. The prevalence of asthma, airflow obstruction on spirometry, and eosinophilic airway inflammation was 21.7%, 12.3% and 15.7% respectively. Women had higher SGRQ-C scores compared to men (15.0 vs 7.7). Wheezing or whistling in the last year and SGRQ-C scores were strongly associated with FeNO levels > 50 ppb after adjusting for age, gender, BMI, and tobacco use. Conclusion: Airway disease is a significant health problem in Kenya affecting a young population without significant tobacco use history.